THE INFLUENCE OF VILLAGE OFFICIALS’ COMPETENCE AND COMMUNITY PARTICIPATION ON THE ACCOUNTABILITY OF VILLAGE FINANCIAL MANAGEMENT: A CASE STUDY OF VILLAGES IN TALAGA JAYA DISTRICT, GORONTALO REGENCY - Nurlyvia H. Ali; Hartati Tuli; Surya Handrisusanto Ahmad (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to examine the effect of village apparatus competence and community participation on the accountability of village financial management in the villages of Talaga Jaya District, Gorontalo Regency. The method used is quantitative with primary data collection through questionnaires distributed to village apparatus with a total sample of 110 respondents. Data processing was carried out using SPSS version 26 with analysis stages including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination tests. The results showed that partially, village apparatus competence has a positive and significant effect on the accountability of village financial management. Similarly, community participation has a positive and significant effect on the accountability of village financial management. Simultaneously, both variables significantly affect accountability of village financial management. These findings have practical implications for village apparatus in Talaga Jaya District to improve accountability through strengthening village apparatus competence and expanding community participation spaces in every stage of financial management, from planning to accountability.